International migration: the human face of globalisation - Keeley, Brian (New Delhi, 2010)
International Migration About 190 million people around the world live outside their country of station birth, These migrants bring energy, entrepreneurship and fresh ideas to our societies. But there are downsides: young migrants who fail in education, adults who don`t find work and, of course, unregulated migration. Such challenges can make migration a political lightning rod and a topic for angry debate. Drawing on the unique expertise of the OECD, this book moves beyond rhetoric to look at the realities of international migration today: Where do migrants come from and where do they go? How do governments manage migration? How well do migrants perform in education and in the workforce? And does migration help-or hinder - developing countries.
Keywords: Migration